B2B brand engagement in social media: The employee's perspective - Pitt, Christine (School of Management Studies, 2017)
Brand engagement, or the process of how customers and other stakeholders form emotional or rational attachments to brands has garnered considerable attention in the marketing literature in recent years. Brand engagement is important because it is a construct strongly related to brand equity, or in simple terms the "value of the brand". Recently, the nature of brand engagement has also changed significantly because of the advent of social media. Not only do users of these social media share personal information with each other, they also comment on, contribute to, and share opinions on the brands that engage them. While the literature is extensive on brand engagement and social media, most of the emphasis is on customers, rather than other stakeholders such as employees, suppliers, and investors. Moreover, the research focuses almost entirely on consumers, the customers of business-to-consumer firms, rather than on the industrial and organizational customers of business-to-business (B2B) firms or their stakeholders. Only very recently have scholars begun to explore both customer and employee engagement and their effects on firm performance in both the business-to-consumer and business-to-business arenas. The research presented in this dissertation attempts to grow the literature in two ways. First, it focuses on brand engagement in business-to-business firms rather than business-to-consumer; second, it does this by studying a stakeholder group other than customers, namely, employees. Moreover, it does this through the employee lens, rather than the lens of the firm; in other words it explores how employees engage with firms rather than how firms engage with their employees. The study utilizes an exploratory research design focusing on qualitative data. The data consist of job reviews posted by employees of B2B firms on the social medium Glassdoor.com. Glassdoor.com collects company reviews and real salaries from employees of a range of organizations and displays them anonymously, and users are also able to rate their employees on a five-star scale. The firms chosen were based on a ranking study by the research firm Brandwatch, and were split into two groups, namely the 30 top ranked firms, and the 30 bottom ranked firms. These reviews were then analyzed, using Hart's theory of word choice and verbal tone, in DICTION, the content analysis software. The results indicate that there are significant differences between top ranked and bottom ranked firms, and also between top rated and bottom rated firms. Employees of top ranked firms are significantly more optimistic in their reviews, while employees of bottom ranked firms express significantly more certainty, activity and realism. There are no significant differences with regard to commonality. With regard to firm ratings, the employees of highly rated firms are significantly more optimistic, while employees of low rated firms score significantly more on all the other dimensions of word choice and verbal tone. The employees of top ranked firms are significantly less insistent in their reviews but display significantly more embellishment, variety and complexity. Similarly, in the case of firm ratings, highly rated reviews are significantly less insistent, but exhibit significantly more embellishment, variety and complexity. The thesis contributes to academic knowledge in four ways. First, it is the first study to consider brand engagement in the business-to-business environment from an employee perspective. Second, the study contributes by providing a perspective on brand engagement from two sides, namely highly ranked B2B companies and low ranked B2B companies, as well as highly rated B2B companies and low rated B2B companies. It highlights the differences between these two groups with regard to brand engagement. Furthermore, it permits a focus on the differences between employees who rate an employer brand high versus those that rate it low, regardless of how the brand is ranked independently. Stated differently, in a brand engagement context, the study identifies specific dimensions or calculated variables that distinguish high and low rankings and ratings. Third, this is the first study that examines employee brand engagement using Hart's theory of word choice and verbal tone. This means that it employs a robust means of comparing pieces of text, or in this particular case, the text resulting from an employee's review and rating of an employer, as a proxy for employee brand engagement. Fourth, this study is the first to use the DICTION content analysis software to examine employee brand engagement in a business-to-business context. It demonstrates DICTION's ability to operationalize Hart's five dimensions of text, and the calculated variables, as well as confirming DICTION's capacity to handle very large text files. The study also has implications for marketing managers, and for brand executives in the business-to-business arena specifically. First, it enables managers to identify the most important dimensions of brand engagement according to Hart's theory, when employee reviews are posted on social media. When managers are able to discern which dimensions figure prominently in the most highly regarded brands according to employees, they can begin to formulate strategies that might enable them to develop these dimensions in their own environment. Likewise, when they are able to distinguish the dimensions that mark the least highly regarded brands, or the dimensions that occasion negative reviews, they will be able to develop strategies that enable their firms to overcome these effects. Second, the use of data such as that available on Glassdoor will allows managers to compare the nature of their brand engagement to others, such as competitors or firms they wish to benchmark against, and to develop strategies that will enable them to shift their level of brand engagement over time. Third, the results of the study reinforce the notion that brands and human capital are more important and interlinked than most managers acknowledge. The management of these two assets therefore requires more than occasional attention; rather, they should become part of regular organizational brand strategy.